2021
DOI: 10.1016/j.devcel.2021.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Polyploid mitosis and depolyploidization promote chromosomal instability and tumor progression in a Notch-induced tumor model

Abstract: Highlights d Active Notch induces polyploid imaginal ring cells to re-enter mitosis d Polyploid mitosis, endoreplication, and depolyploidization together promote tumor growth d Ploidy-reduction division depends on genes involved in DNAdamage response and repair d Tumor progression correlates with increased ploidy heterogeneity and polyaneuploidy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 88 publications
2
17
0
Order By: Relevance
“…Although the causal relationship between aneuploidy and tumors is uncertain at present, studies have found that aneuploid cells with genomic instability may even exhibit the ability to proliferate indefinitely, similar to cancerous cells [70,74,75]. A recent study found that induction of Notch signaling in polyploid cells leads to malignant proliferation, loss of cell polarity, and further development into tumors with high genomic instability [76]. Interestingly, our study shows that genes associated with the Notch signaling pathway are abnormally expressed in aneuploidy Drosophila (Figures 2D and 3), suggesting a close association between aneuploidy and tumor formation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the causal relationship between aneuploidy and tumors is uncertain at present, studies have found that aneuploid cells with genomic instability may even exhibit the ability to proliferate indefinitely, similar to cancerous cells [70,74,75]. A recent study found that induction of Notch signaling in polyploid cells leads to malignant proliferation, loss of cell polarity, and further development into tumors with high genomic instability [76]. Interestingly, our study shows that genes associated with the Notch signaling pathway are abnormally expressed in aneuploidy Drosophila (Figures 2D and 3), suggesting a close association between aneuploidy and tumor formation.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, data obtained from synthetic autotetraploid plants (watermelon, soybean, and Arabidopsis) also indicate that polyploidy shifts the A-to-B chromatin balance toward the actively transcribed A-chromatin [ 106 , 107 ]. Moreover, recent studies provide evidence that genome duplications reorganize topologically associated domains (TAD) packaged within A- and B-chromatin compartments via the increase in intra-TAD interaction and reorganization of chromatin loops [ 106 , 108 ]. In addition, polyploidy in giant cancer cells can enlarge chromosome territories [ 109 ].…”
Section: Myc and Polyploidy Promote Chromatin Openingmentioning
confidence: 99%
“…These studies reveal a blurring of the lines between what constitutes a bona fide meiosis versus a meiosis-like process. Similar ploidy reduction processes occur in polyploid cancer cells where meiosis and recombination genes are again implicated, suggesting that related depolyploidization mechanisms occur across eukaryotes [ 2 , 3 ]. For example, a number of meiosis-specific genes (including DMC1, SPO11, and REC8) have been found to be activated during depolyploidization of polyploid tumor cells [ 36 ].…”
Section: What Drives Ploidy Changes In Pathogenic Fungi?mentioning
confidence: 99%
“…For example, increased ploidy levels frequently occur in certain organs of both animals and plants [ 1 ]. In many human tumors, especially some high-grade tumors, changes in ploidy are common and have been suggested to contribute to tumorigenesis [ 2 , 3 ]. Human fungal pathogens are a major threat to human health and cause not only superficial diseases but also life-threatening invasive or systemic infections.…”
Section: Introductionmentioning
confidence: 99%